Scientific Article Writing Training for Teachers of State Elementary School 2 Liligundi - Werang, Basilius Redan; Utami, Ketut Herya Darma; Sukmayasa, I Made Hendra; Rupiana, I Nyoman Sugita; Wati, Ni Nyoman Kurnia (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this training activity is to improve the understanding and skills of teachers at SDN 2 Liligundi in writing scientific articles. The number of participants in this training is 10 people. This training activity will be carried out using a face-to-face method. The data collection method used to measure the success of this training is the training assignment method and questionnaire. While the data analysis method used is the quantitative descriptive data analysis method. The indicator of the success of this training is the increasing ability of teachers at SDN 2 Liligundi in compiling scientific articles, especially scientific articles from research they have conducted at school. The results of this training are to improve the understanding and skills of teachers at SDN 2 Liligundi in writing scientific articles, especially scientific articles sourced from Classroom Action Research that has been carried out by teachers. It can be concluded that the scientific article writing training activity for teachers at SDN 2 Liligundi has gone very well and is beneficial for improving teacher professionalism in compiling scientific articles.